Polymeric nanocomposite: Development, characterization, ex vivo and in vivo evaluation for ulcerative colitis. Issue 7 (2nd May 2016) - Gulbake, Arvind; Chashoo, Gousia; Sharma, P. R.; Gupta, Prem N.; Saxena, A. K.; Jain, Sanjay K.
ABSTRACT: Chitosan nanoparticles (CH-NPs) and chitosan-montmorillonite nanocomposites (CH-MMT-NCPs) were developed and characterized. The in vitro drug release data revealed that the CH-MMT-NCPs successfully retarded the drug release until it entered into the simulated colonic fluid. Experimental colitis was induced by trinitrobenzenesulfonic acid (TNBS) into albino rats and clinical activity score and histological evaluation revealed that the CH-MMT-NCPs markedly improved the healing efficacy as compare to CH-NPs and drug solution. The CH-MMT-NCPs showed remarkable reduction in the ulcer index (3.80 ± 0.54) as compared to the CH-NPs (7.03 ± 0.78) and the group received MSZ solution (9.85 ± 0.58), respectively. GRAPHICAL ABSTRACT: